Multi-material topology optimization for composite metal aircraft structures - Liu, Cheng; Yasaee, Mehdi; Dayyani, Iman (Cranfield University, 2017)
This paper investigates an optimization routine for lightweight composite-metal hybrid aircraft structures. This routine is developed based on two existing topology optimization approaches, Moving Morphable Components (MMC) and level set method updated by a reaction diffusion equation. The proposed method overcomes the weakness of conventional multi-material optimizers by introducing some rules of material distribution, that enhance the manufacturability of the optimal structure. It is achieved by optimizing the main structural frame using uniform-width components first, leaving the joints as void together with the remaining design domain, and following by a conventional topology optimization using single-material level set approach. A commonly used beam model is optimized to demonstrate the key ideas of the proposed routine.
Keywords: Topology optimization; Multi-material; Aircraft structure; Finite elements